Can Sámi braiding constitute a basis for teaching discrete mathematics? Teachers and researchers’ investigations - Fyhn, Anne Birgitte; Jannok Nutti, Ylva; Dunfjeld, Maja Hilma; Eira, Ellen J. Sara; Steinfjell, Ann Synnøve; Børresen, Tove; Hætta, Ole Einar Isaksen; Sandvik, Svein Ole (North American Study Group on Ethnomathematics, 2017)
Source at https://journalofmathematicsandculture.wordpress.com/2017/12/28/journal-of-mathematics-and-culture-volume-11-number-4/ . A group of Sámi middle school mathematics teachers cooperated with researchers over a period of three years in investigating ruvden (Sámi braiding). The aim was to find possibilities for teaching discrete mathematics based on ruvden. The Sámi are an Indigenous people of the Arctic and their braidings are intertwined with Sámi traditional knowledge. The teachers presented two different approaches to the ruvden procedure. One researcher presented a third approach and later, two students came up with a fourth. The analysis reveal that a) the four approaches reflect different aspects of Sámi traditional knowledge and b) investigations of ruvden may lead to two aspects of discrete mathematics; transitions from numbers to variables and combinatorics.